Altered BAF occupancy and transcription factor dynamics in PBAF-deficient melanoma - Carcamo, Saul; Nguyen, Christie B.; Grossi, Elena; Filipescu, Dan; Alpsoy, Aktan; Dhiman, Alisha; Sun, Dan; Narang, Sonali; Imig, Jochen; Martin, Tiphaine C.; Parsons, Ramon; Aifantis, Iannis; et al. (Cell reports (Cambridge), 2022)
ARID2 is the most recurrently mutated SWI/SNF complex member in melanoma; however, its tumor-suppressive mechanisms in the context of the chromatin landscape remain to be elucidated. Here, we model ARID2 deficiency in melanoma cells, which results in defective PBAF complex assembly with a concomitant genomic redistribution of the BAF complex. Upon ARID2 depletion, a subset of PBAF and shared BAF-PBAF-occupied regions displays diminished chromatin accessibility and associated gene expression, while BAF-occupied enhancers gain chromatin accessibility and expression of genes linked to the process of invasion. As a function of altered accessibility, the genomic occupancy of melanoma-relevant transcription factors is affected and significantly correlates with the observed transcriptional changes. We further demonstrate that ARID2-deficient cells acquire the ability to colonize distal organs in multiple animal models. Taken together, our results reveal a role for ARID2 in mediating BAF and PBAF subcomplex chromatin dynamics with consequences for melanoma metastasis. [Display omitted] •ARID2 loss results in impaired PBAF complex assembly and BAF genomic redistribution•Altered SWI/SNF dynamics results in chromatin accessibility and TF binding changes•PBAF loss drives an invasive gene expression signature and phenotype in melanoma The tumor-suppressive functions of the SWI/SNF subunit ARID2 remain ill-defined in the context of melanoma. Carcamo et al. demonstrate that, upon ARID2 depletion, the PBAF complex fails to assemble, altering BAF genomic occupancy with consequences on chromatin accessibility, transcription factor binding, and transcriptional changes that promote metastasis.